Heparan sulfate regulates amphiregulin programming of tissue reparative lung mesenchymal cells during influenza A virus infection in mice - Lucas F. Loffredo; Anmol Kustagi; Olivia R. Ringham; Fangda Li; Kenia de los Santos-Alexis; Anjali Saqi; Nicholas Arpaia (Nature Communications)
Abstract Amphiregulin (Areg), a growth factor produced by regulatory T (Treg) cells to facilitate tissue repair, contains a heparan sulfate (HS) binding domain. How HS, a highly sulfated glycan subtype that alters growth factor signaling, influences Areg repair functions is unclear. Here we report that inhibition of HS in various cell lines and primary lung mesenchymal cells (LMC) qualitatively alters Areg downstream signaling. Utilization of a panel of cell lines with targeted deletions in HS synthesis–related genes identifies the glypican family of HS proteoglycans as critical for Areg signaling. In the context of influenza A virus (IAV) infection in vivo, an Areg-responsive subset of reparative LMC upregulate glypican-4 and HS; conditional deletion of HS primarily within this LMC subset results in reduced repair characteristics following IAV infection. This study demonstrates that HS on a specific lung mesenchymal population is a mediator of Treg cell–derived Areg reparative signaling.